Fine Motor Development In Toddlers - Satriyandari, Yekti; Dulasdi, Nur Ain Desta (Prosiding University Research Colloquium, 2022)
The degree of children health reflects the health of the nation because children as the successor to the nation have the ability to be developed in continuing development of the nation. The problem is that not all children get through the process of development properly. Their developmental are delayed due to the lack of parents’ recognition of the danger signs (redflag) in their children development, early detection checks or development screening in children, and direct involvement of parents in their children world or stimulation from non-parents. The purpose of this study is to see the development of children aged 1-5 years. This type of quantitative. The sampling technique used in this study was non probability sampling method called purposive sampling and was calculated by the number of samples in this study as 50 people. The analysis was carried out using univariate analysis. The results showed that the description of motoric development of children aged 1-5 years in the Jowah V Maternal Health Unit, most of the measurement of children development were normal with fine motor development as 94.2% of toddler development who had untestable categories of 3 children with a percentage of 5.8%, Jowah V Maternal Health Unit needs to establish cooperation with health workers / health agencies for routine children development checks / DDST II so that mothers of toddlers know about their children development regularly.